Designing polydopamine nanohybrid based on template-mediated for effectively remove amphetamine-type stimulants in sewage: Performance and mechanism. Issue 5 (October 2021) - Tian, Yu; Cao, Shurui; Xi, Cunxian; Su, Hongtao; Chen, Zhiqiong
Abstract: In this study, a novel strategy of template-mediated was proposed to fabricate mussel-inspired chemistry magnetic polydopamine nanohybrid (magGO/PDA) through graphene oxide (GO) sheet tailored graft polymerization of dopamine. Characterization of the nanohybrid was carried out and compared with solely magnetic polydopamine (magPDA), as well as amphetamine-type stimulants (ATS) adsorption performances and principle adsorption mechanisms in sewage were studied in detail. The results showed that magGO/PDA exhibited superior adsorption capacities for ATS (333.110 μg g - 1, 343.556 μg g - 1 and 364.853 μg g - 1 for AMP, MAMP and MDMA respectively), which attributed to the template effect of GO whose offered large surface to regulate the growth of polydopamine functional material, resulted more adsorption active sites. The kinetics data fitted well with the pseudo-second order model indicated the adsorption of ATS was chemisorption on homogeneous surface of such material. Adsorption mechanism indicated that the hydrogen-bond between –O - groups of adsorbent and amino groups of ATS played the main role, as well as π-π stacking provided part of the driving forces. Response surface methodology (RSM) was selected to optimize experimental parameters affecting adsorption performances. Summarily, this work provided a novel idea to design superb polydopamine nanohybrid by template-mediated. Graphical Abstract: ga1 Highlights: Polydopamine nanohybrids had been synthesized by means of template-mediated and tailored graft polymerization of dopamine. Template effect of graphene oxide provided significant contribution to adsorption. Response surface methodology (RSM) had been selected to obtain the optimal adsorption conditions. Kinetic, isotherm and thermodynamic studies had been carried out to characterize ATS adsorption performance. The hydrogen-bond between the –O - groups of adsorbent and the amino groups of ATS played a major role in adsorption.